Selection of Intratextual Audience for Poems in Constitutional Period (Based on personal experience of poets) - mohsen zolfaghari (Matn/Pizhūhī-i Adabī, 2012)
The present paper discusses how the intratextual audience is selected based on the personal experiences of some prominent poets of the Constitutional era. The research questions are: 1. Which aspects of personal experiences did mostly affect the audience selection by the poets? 2. Did different experiences lead to distinction of style in selecting the audience? A deductive methodology is selected to carry out this research, in which different audience types; particularly intratextual ones are categorized and defined, once the works of the poets in Constitutional period are carefully studied. Then, the biographies of these poets are used as data providing personal experiences. The data is presented with focus on family, education and studies, beliefs and social roles, and the effect of these experiences on selection of intratextual audience are discussed. The result shows that personal experiences lead to differences in style when it comes to audience selection. A closes analysis of the method of selection reveals the thoughts and worldview of the artist. The structure and frequency of different intratextual audiences also show the identity of the poet’s potential or ideal audience.